BENTUK PERLAKUAN PATRON TERHADAP KLIEN DALAM PERDAGANGAN KAYU MANIS DI PASAR NAGARI KABUPATEN TANAH DATAR (JURNAL SPASIAL, 2014)
The purpose of this study was to determine and analyze any form of treatment patron of the client in the cinnamon trade in Nagari Pasar Tanah Datar. The research is a qualitative research, the naturalistic or natural, it is done on a particular natural background, and has a particular case. The results of the research are: 1). Rooted historically to trading activity in the village market, especially with the Client Patron export commodities traders. 2). Having a wide network klientisasi in control of the business, has the ability to build reciprocity to strengthen social insurance with business partners. 3). Patron business network and market traders in villages Clients who trade export crops can be used as a base to develop the agricultural product processing industry whose market is wide open in the ASEAN and China. 4). The creation of a network of business groups klientisasi to village markets can be a forerunner to form a business network Minangkabau to compete with China's business network, in exploiting investment opportunities provided by the government of West Sumatra. 5). With the capability of reciprocity and social insurance held so far, can create business linkages (business leakage) with groups of businesses along the corridor of Sumatra.Keywords: Treatment, clients, cinnamon